Representasi Kekerasan Simbolik Pada Animasi The Spongebob Squarepants - Agusty, Muhammad Danny Setyo; Jacky, M (Paradigma, 2024)
This research aims to identify the representation of symbolic violence in the SpongeBob SquarePants animation. It is a qualitative descriptive study using content analysis method and data collection techniques involving observation and documentation. The research employs Pierre Bourdieu’s theory of symbolic violence. The object of the study is scenes in the SpongeBob SquarePants animation that contain instances of violence.The results of the study indicate the presence of symbolic violence. According to Pierre Bourdieu, symbolic violence takes forms such as power domination, discrimination, and language. These forms of symbolic violence are depicted through scenes involving images, texts, symbols, or actions. Firstly, in the domination of power, Mr. Krabs is shown to have full authority to establish rules that benefit himself and harm his employees. Secondly, discrimination is exemplified by the character Craig, who does not allow SpongeBob to enter his party due to their lighter skin, demonstrating discriminatory and racist behavior. Thirdly, language-based symbolic violence is illustrated through framing, where language is used to degrade individuals, such as when Patrick is insulted by customers, calling him foolish. Keywords: Representation, Movie, Symbolic Violence